Menjaga privasi pengguna rumah dengan penerapan secondary skin pada fasad - Lestari, Wiji Suci (Maliki Interdisciplinary Journal, 2024)
Privacy is very important for individuals and users because privacy serves to protect oneself and limit communication with others. In daily life, privacy is needed for users who live in a building. The activities carried out in the residence are not only used by individuals but also the interaction of users who live in it and also interact with other users. So, this can be overcome by the application of secondary skin on the building facade so that user privacy is maintained. In addition to maintaining user privacy, the use of secondary skin in buildings can beautify the appearance of the building because it can add aesthetic elements to the facade of a residential house. In connection with the application of secondary skin in residential houses, the purpose of the researcher writing this article is to find out how the function of using secondary skin to maintain the privacy of the users who live in it. The methods taken in this article is a literature review, namely bringing together data by studying theories and understanding various literatures related to the topic in this study.